2016
DOI: 10.1108/lhs-08-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering paradoxes from physicians’ experiences of patient-centered ward-round

Abstract: Purpose The purpose of this paper is to uncover paradoxes emerging from physicians' experiences of a patient-centered and team-based ward round, in an internal medicine department. Design/methodology/approach Abductive reasoning relates empirical material to complex responsive processes theory in a dialectical process to further understandings. Findings This paper found the response from physicians, to a patient-centered and team-based ward round, related to whether the new demands challenged or confirmed indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
(24 reference statements)
0
11
0
1
Order By: Relevance
“…Then new patterns of thinking and behaving can be developed in the organization [ 36 ]. It is important for managers to understand and respect that contradictory opinions can exist at the same time in the same organization [ 37 ] in order to facilitate the process of change.…”
Section: Discussionmentioning
confidence: 99%
“…Then new patterns of thinking and behaving can be developed in the organization [ 36 ]. It is important for managers to understand and respect that contradictory opinions can exist at the same time in the same organization [ 37 ] in order to facilitate the process of change.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation might be that implementing VBHC was seen as a break in the NPM trend. [12,14] Even if concern for the patients is a key to increased engagement by health professionals, [36] this study has solely focused on health professionals as leaders for implementing VBHC. Therefore no answers are given regarding patients' experiences of the implementation of VBHC.…”
Section: Discussionmentioning
confidence: 99%
“…Here physician vulnerability becomes exposed as grief, which may induce embarrassment and shame (25), or loneliness and powerlessness as part of professional responsibility (26). In a qualitative study following an intervention to change the ward-round routines in a Swedish hospital to reduce medical errors, it was found that the attending physicians' ability to adjust to the new routines was better when they applied a "We-perspective" rather than an "I-perspective" on their work (27). The former perspective was characterized by a focus on teamwork, other providers' input was considered essential, and conversation with the patient was given priority compared to reading the record.…”
Section: Discussionmentioning
confidence: 99%
“…Medical culture in the scientific era may have developed an unhealthy aim of eliminating uncertainty (28). If staying in control is the overarching paradigm of the working climate you are part of, loss of control means loss of confidence from peers and represents a major threat to your position and sometimes identity (17,27,29). It probably takes repeated unpleasant emotional experiences before many physicians are able to recognize and acknowledge their own vulnerability.…”
Section: Discussionmentioning
confidence: 99%